2015
DOI: 10.1016/j.quascirev.2015.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Lake sediment multi-taxon DNA from North Greenland records early post-glacial appearance of vascular plants and accurately tracks environmental changes

Abstract: a b s t r a c tHigh Arctic environments are particularly sensitive to climate changes, but retrieval of paleoecological data is challenging due to low productivity and biomass. At the same time, Arctic soils and sediments have proven exceptional for long-term DNA preservation due to their constantly low temperatures. Lake sediments contain DNA paleorecords of the surrounding ecosystems and can be used to retrieve a variety of organismal groups from a single sample. In this study, we analyzed vascular plant, br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 73 publications
(107 reference statements)
1
74
0
Order By: Relevance
“…Sequences from ‘food or cultivated plants’ and taxa ‘highly unlikely to have been present’ were excluded by Epp et al . ().…”
Section: Adna As the Sole Basis For Floristic Reconstructionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Sequences from ‘food or cultivated plants’ and taxa ‘highly unlikely to have been present’ were excluded by Epp et al . ().…”
Section: Adna As the Sole Basis For Floristic Reconstructionsmentioning
confidence: 97%
“…Picea DNA was recorded and interpreted as contamination by pollen carried into the DNA extraction laboratory. Epp et al (2015) found aDNA of 17 vascular plants and eight bryophyte taxa from Holocene sediments from a high Arctic lake in northern Greenland. The determinations were mainly at a generic or family level with five species identifications.…”
Section: New Phytologistmentioning
confidence: 99%
“…Qubit ® Fluorometer is widely used for DNA quantification in many previous studies due to its accuracy and sensitivity. [9][10][11][12][13] Total DNA yields from DNA standards using 2 different DNA extraction methods in forensic DNA analysis, QIAmp DNA kit is widely employed for DNA extraction since it allows for quick and easy extraction. However, we hypothesized that the kit may yield low amounts of DNA due to the fact that DNA is usually lost during the DNA-membrane binding process, washing and DNA elution.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the most stringent efforts, however, contamination can still occur and may be more likely when working with ubiquitous commercial crops, such as members of the Triticeae 4748. This is particularly problematic given many charred archaeobotanical studies aim to investigate aspects of historical domestication and the spread of agriculture in these species26.…”
Section: Discussionmentioning
confidence: 99%